2008
DOI: 10.1021/jp808279j
|View full text |Cite
|
Sign up to set email alerts
|

Functional Multilayered Transparent Conducting Oxide Thin Films for Photovoltaic Devices

Abstract: In this study, we present a thermally stable multilayered transparent conducting oxide (TCO) functionalized for dye-sensitized solar cells (DSSCs). Nb-doped TiO2 (NTO) layers deposited on conventional Sn-doped In2O3 (ITO) substrates using pulsed laser deposition (PLD) enhanced the optical-to-electrical conversion efficiency of the DSSCs by as much as 17% compared to that of bare ITO-based DSSCs. The electrical properties and J−V characteristics of the multilayered NTO/ITO films showed that the improved cell pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
35
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(35 citation statements)
references
References 18 publications
0
35
0
Order By: Relevance
“…Nb‐doped TiO 2 also has been shown to hold promising applications in transparent conducting oxides (TCOs),7, 8 antistatic materials, and gas sensors 9, 10. Recently, Fujishima and coworkers reported that a Nb‐doped TiO 2 (NTO) film could be used as a favorable electron‐transfer mediator in photovoltaic devices,11 which was further testified by other research groups 12–14. However, few studies have been reported on the positive role of Nb‐doped TiO 2 nanoparticles when applied as the photoanode material of DSSCs, and the mechanism of the effects caused by ion doping is still controversial.…”
Section: Introductionmentioning
confidence: 99%
“…Nb‐doped TiO 2 also has been shown to hold promising applications in transparent conducting oxides (TCOs),7, 8 antistatic materials, and gas sensors 9, 10. Recently, Fujishima and coworkers reported that a Nb‐doped TiO 2 (NTO) film could be used as a favorable electron‐transfer mediator in photovoltaic devices,11 which was further testified by other research groups 12–14. However, few studies have been reported on the positive role of Nb‐doped TiO 2 nanoparticles when applied as the photoanode material of DSSCs, and the mechanism of the effects caused by ion doping is still controversial.…”
Section: Introductionmentioning
confidence: 99%
“…Recent discovery of metallic conductivity and high optical transparency in Nb‐doped anatase TiO 2 (Nb:TiO 2 ) stimulated intense research on this material 33,34 for their applications as transparent conducting oxides 35–40 . The Nb 5+ is an n ‐type dopant for TiO 2 , modifies the band structure of TiO 2 , and generates additional carriers in its conduction band 34,41 .…”
Section: Introductionmentioning
confidence: 99%
“…[23][24][25][26][27][28][29][30][31][32] Recent discovery of metallic conductivity and high optical transparency in Nb-doped anatase TiO 2 (Nb:TiO 2 ) stimulated intense research on this material 33,34 for their applications as transparent conducting oxides. [35][36][37][38][39][40] The Nb 51 is an n-type dopant for TiO 2 , modifies the band structure of TiO 2 , and generates additional carriers in its conduction band. 34,41 The band structure calculations report that the 4d orbitals of Nb strongly hybridize with the 3d ones of Ti and form a d-natured conduction band, which is thought to be the origin of metallic conductivity in this material.…”
Section: Introductionmentioning
confidence: 99%
“…Then, the band bending at the interface between TiO 2 nanoparticles and NTO-NFs is expected to promote the carrier transfer at the interface [8,9]. In the present study, we added ES-NFs of TiO 2 and NTO to the dye-sensitized layer of mesoporous TiO 2 in conventional DSCs, and examined their effects to the photovoltaic characteristics.…”
Section: Introductionmentioning
confidence: 94%